Projective/Spontaneous: 4 Pomes from the EZ-Chair (AmeriQuests, 2010)
Written under Buddhic trance on derelict typewriter, these pomes offer fruit. Origin process includes: Olson's theories of projective verse, Kerouac's "first thought best thought," Ginsberg's mad poetry, other ghosts' murmurs. Scribed in mode of joyousness. The Beats were not vegetables. Enjoy with wine.